2007
DOI: 10.1007/s00278-007-0565-7
|View full text |Cite
|
Sign up to set email alerts
|

Die Bindungstheorie und ihre Relevanz für die Psychotherapie

Abstract: Bei dieser Arbeit handelt es sich um die modifizierte Fassung eines Kapitels für das von B. Strauß herausgegebene Buch Bindung und Psychopathologie -Relevanz der Bindungstheorie für die psychotherapeutische Praxis, Klett Cotta, Stuttgart, 2008. Wir danken dem Verlag für die freundliche Abdruckgenehmigung.Übersichten Als vor 10 Jahren in dieser Zeitschrift die Frage nach der Bedeutung der Bindungstheorie für die Psychotherapie in Form zweier Übersichten erörtert wurde (Schmidt u. Strauß 1996; Strauß u. Schmidt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 97 publications
1
4
0
2
Order By: Relevance
“…At the end of therapy, nearly two thirds of the patients showed a secure attachment style - which is in accordance with the rates of secure attachment found among children and adolescents in epidemiological samples. Our results also confirm the results of two other studies: those reported by Strauss and Schwark [10] regarding the ability of attachment style to be changed in adult patients and the results reached by Hoffman et al [9] with infants and small children. The rate of 40% of children and youths changing from insecure to secure attachment styles also matches the rate reported by Fonagy et al [8] for adult patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At the end of therapy, nearly two thirds of the patients showed a secure attachment style - which is in accordance with the rates of secure attachment found among children and adolescents in epidemiological samples. Our results also confirm the results of two other studies: those reported by Strauss and Schwark [10] regarding the ability of attachment style to be changed in adult patients and the results reached by Hoffman et al [9] with infants and small children. The rate of 40% of children and youths changing from insecure to secure attachment styles also matches the rate reported by Fonagy et al [8] for adult patients.…”
Section: Discussionsupporting
confidence: 83%
“…At the end of the parents' treatment, the children with a disorganized attachment style exhibited an organized and - in many cases - a secure attachment style. A summary of the results of the changes in attachment styles after psychotherapy in adult patients can be found in the study by Strauss and Schwark [10]. With the exception of the study by Fonagy et al [8], the percentage of patients who successfully changed their attachment style from insecure to secure over the course of therapy was just under one third.…”
Section: Introductionmentioning
confidence: 95%
“…Another limitation concerns data collection since we only used self-report data. Although the instruments we used are evaluated as high-quality, studies have suggested that the results of self-­report measures and expert ratings may differ [59, 60]. Future research should consider this fact and verify our results by using interview measures, such as the Adult Attachment Interview [61], and expert ratings, such as the Reflective Functioning Scale [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Zukunft soll das Material auch noch im Hinblick auf Prozesscharakteristika untersucht werden. Es kann aufgrund mehrerer Studien davon ausgegangen werden, dass Bindungsmerkmale sowohl die therapeutische Beziehung als auch interaktive Prozesse in der Psychotherapie beeinfl ussen [48] .…”
Section: Behandlungenunclassified